Damage-control steel frames equipped with SMA connections and ductile links subjected to near-field earthquake motions: A spectral energy factor model. (15th July 2021) - Zhou, Xuhong; Zhang, Huanyang; Ke, Ke; Guo, Lihua; Yam, Michael CH
Highlights: The novel structure showing the partially self-centring behaviour was proposed. A spectral energy factor model for the system was developed based on the lognormal distribution assumption. The sufficiency of the energy factor model was justified. Abstract: To achieve a delicate balance between self-centring behaviour and energy dissipation, it was proposed to develop the damage-control steel frame equipped with shape memory alloy (SMA) connections and ductile links showing the partially self-centring behaviour. This paper examined the inelastic seismic demand of the novel structure, and the emphasis was given to the spectral energy factor of the system subjected to near-field earthquake motions. Based on single-degree-of-freedom (SDF) systems representing the novel structure and a near-field earthquake database, nonlinear spectral analyses were performed considering a wide range of structural period and hysteretic parameters, and more than 25 million energy factors were obtained. The probabilistic characteristics of the energy factors were examined in detail. The analysis database confirmed that the energy factors were sensitive to structural period and hysteretic parameters. In addition, a right-skewed distribution feature of the energy factors was observed. Thus, a spectral energy factor model for damage-control steel frames equipped with SMA connections and ductile links was developed using the lognormal distribution model. Nonlinear regression analyses were conducted to develop a series of prediction equations. The good agreement between the histograms of the energy factor and predictions by the regression equations confirmed the adequacy of the proposed model. The proposed model was eventually applied to evaluating the damage-control behaviour of a prototype structure under near-field earthquake motions, and the sufficiency of the model for assessing the structural damage-control behaviour from a statistic perspective was confirmed.